2016
DOI: 10.5812/aapm.39495
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Postoperative Pain in Pediatric Operations: Comparing the Efficiency of Bupivacaine, Bupivacaine-Dexmedetomidine and Bupivacaine-Fentanyl for Caudal Block

Abstract: BackgroundCaudal analgesia is a common method for postoperative pain management in pediatric patients. Additive agents such as opioids and α2 agonists have been used to enhance the analgesic effects of local anesthetics for caudal block.ObjectivesThe aim of this study was to compare the additive effects of dexmedetomidine and fentanyl on bupivacaine-induced caudal analgesia in pediatric patients who had undergone elective inguinal hernia repair.MethodsThis randomized, double-blind clinical trial included child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…Giving our concern for a possible neurotoxicity from neuraxial dexmedetomidine, we selected a dose of 1 µg/kg similar to the study done by Hou et al, which suggested that low doses of intrathecal dexmedetomidine (0.75:1.50 µg/kg) can relieve pain without the risk of neurotoxicity [7]. Al-Zabenetal also mentioned that caudal dexmedetomidine in a dose of 1 µg/kg was comparable to the dose of 2 µg/kg regarding to the prolongation of postoperative analgesia, with shorter duration of postoperative sedation, lower incidence of side effects, and devoid of neurotoxicity [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Giving our concern for a possible neurotoxicity from neuraxial dexmedetomidine, we selected a dose of 1 µg/kg similar to the study done by Hou et al, which suggested that low doses of intrathecal dexmedetomidine (0.75:1.50 µg/kg) can relieve pain without the risk of neurotoxicity [7]. Al-Zabenetal also mentioned that caudal dexmedetomidine in a dose of 1 µg/kg was comparable to the dose of 2 µg/kg regarding to the prolongation of postoperative analgesia, with shorter duration of postoperative sedation, lower incidence of side effects, and devoid of neurotoxicity [8].…”
Section: Discussionmentioning
confidence: 99%
“…It appears to be less neurotoxic than other existing agents and has the potential to be neuroprotective in the neonatal and paediatric settings [6]. Its selectivity for α 2-adrenoceptor makes it much more effective sedative and analgesic agent than clonidine [7]. This selectivity is mainly responsible for the proposed neuroprotective effects of dexmedetomidine [8].…”
Section: Introductionmentioning
confidence: 99%
“…They noticed no side effects like hypotension, bradycardia, pruritus, nausea, vomiting, and urinary retention in their study. 18 In our study, the dose of bupivacaine is 0.75 mL/kg instead of 1 mL/kg in their study. The doses of dexmedetomidine and fentanyl in our study were 1 mcg/kg instead of 2 mcg/kg in their study.…”
Section: Discussionmentioning
confidence: 85%
“…Local anesthetics such as bupivacaine and ropivacaine were used for peripheral nerve block, sympathetic nerve block, local in ltration, epidural and caudal blocks [11,[26][27][28]. Combination dexmedetomidine with bupivacaine or ropivacaine can prolong the analgesic effect [14,29,30]. In a prospective randomized study involving 60 patients with the age between 6 months to 6 years scheduled for unilateral inguinal herniorrhaphy, the duration of analgesia is signi cantly higher in patients receiving bupivacaine with dexmedetomidine in comparison to patients receiving bupivacaine alone, but the frequency of analgesic consumption in the rst 24 h and total dose of analgesic consumption had no signi cant difference in the two groups [11].…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine, a strong α2 adrenergic agonist, has a sympatholytic, sedative, analgesic effect and is effective in many anesthetic and analgesic techniques [12,13]. The addition of dexmedetomidine to wound in ltration with ropivacaine was reported to reduce post-operative pain after inguinal herniorrhaphy [14][15][16].…”
Section: Introductionmentioning
confidence: 99%